Implementasi Backup Image VM Pada Proxmox Virtual Environment (Promox VE) Untuk Kebutuhan Server - Molavi Arman; Novan Wijaya (BETRIK, 2026)
Data availability and security are crucial aspects of information technology infrastructure management, especially in virtualization-based server environments. Proxmox Virtual Environment (Proxmox VE), as an open-source virtualization platform, provides Virtual Machine (VM) image backup features that can be used to improve system reliability. However, the implementation of scheduled backups integrated with external storage media has not been widely studied, particularly from the perspective of operational processes and system management. This study aims to describe the implementation of VM image backup on Proxmox VE using the scheduled backup feature combined with the Samba protocol as storage media on a separate server. This study employs a qualitative descriptive approach with the PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) methodology as the research framework. Data were collected through system observation, configuration documentation, and analysis of backup operational  processes. System testing was carried out through SMB/CIFS storage access testing, scheduled backup execution testing on selected VMs, Proxmox VE log verification, and inspection of backup files stored on Samba storage. The implementation results show that Samba storage was successfully integrated with Proxmox VE and that the VM image backup process could run automatically according to the configured schedule, with backup files successfully stored on the target media and recorded in the system logs. This implementation improves backup storage reliability, minimizes the risk of data loss, and simplifies backup server management. This study is expected to provide a practical reference for implementing Proxmox VE-based backup servers for system administrators and institutions.